MEASURING APPLICATION AUGMENTED REALITY TO INCREASE MSME PERFORMANCE USING TECHNOLOGY ACCEPTANCE MODEL - Setyorini, Noni; Violinda, Qristin; Ulumudin, Arisul; Wattegama, Erandi Jinadari (Jurnal Aplikasi Manajemen, 2022)
This study aimed to examine the effect of perceived usefulness and perceived ease to use on the performance of MSMEs in Ngerangan Village, Klaten, with trust as a mediator. The data collection method used is probability sampling with a saturated sampling technique. The total respondents in the study were 100 respondents, which is MSME in Ngerangan Village. Hypothesis testing using smartPLS software. The study results are perceived usefulness and perceived ease of use affect trust. Likewise, trust influences the performance of MSMEs in Ngerangan Village. However, perceived usefulness does not directly affect the performance of MSMEs. In contrast to perceived ease to use, which directly influences the performance of MSMEs. The practical implications of this research are that the technology adopted by MSMEs must be easy to use and have many benefits for business development.